Turks across empires: marketing Muslim identity in the Russian-Ottoman borderlands, 1856-1914 - Meyer, James H. (Oxford studies in modern European history, 2015)
This book traces the paths of Muslim community activists from Russia who followed a wave of revolutions unfolding in Russia (1905), Iran (1906), and the Ottoman Empire (1908). Centered on the lives and careers of İsmail Gasprinskii, Yusuf Akçura, and Ahmet Ağaoğlu, this book tells a wide-ranging story about the late imperial era in the Russian-Ottoman borderlands. Honing in on bigger developments taking place in the region from the end of the Crimean War until the beginning of World War I, the book discusses events occurring in central Russia, Crimea, the Caucasus, and the Ottoman Empire. Situating these future icons of Turkish and pan-Turkic identity within the broader contexts, the book examines changes happening in the region with respect to trans-imperial border crossing, an outbreak of revolutions, and what the book calls the politicization of “civilizational” identity. This book then connects the late imperial to our own, arguing that the post-Cold War has much in common with the time of the pan-Turkists. Drawing upon a wide array of sources in Russian and the Turkish languages of the Russian-Ottoman borderlands, this book explores bigger questions concerning the lessons that the post-Cold War world can learn from the hyper-politicized identity struggles of the late imperial era. The lives and experiences of Gasprinskii, Akçura, Ağaoğlu, and their comrades were fascinating and frenetically paced.